2017
DOI: 10.1113/ep086203
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging evaluation of renal ischaemia–reperfusion injury in a rabbit model

Abstract: What is the central question of this study? Renal ischaemia-reperfusion injury occurs in various clinical settings. The clinical diagnosis of ischaemia-reperfusion injury is routinely based on biochemical and haematological tests, which cannot evaluate the function of a single kidney. New magnetic resonance imaging techniques to identify the pathophysiological changes in the renal outer medulla were evaluated. What is the main finding and its importance? This study demonstrated that susceptibility-weighted ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…A previous study found obvious changes in the renal outer medulla on SWI after renal IRI, and the integrity of the hypointense outer medulla on SWI showed significant differences at various time points after IRI 12 . This study further investigated the correlation between renal IRI on SWI with histopathology.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A previous study found obvious changes in the renal outer medulla on SWI after renal IRI, and the integrity of the hypointense outer medulla on SWI showed significant differences at various time points after IRI 12 . This study further investigated the correlation between renal IRI on SWI with histopathology.…”
Section: Discussionmentioning
confidence: 82%
“…24 A previous study found obvious changes in the renal outer medulla on SWI after renal IRI, and the integrity of the hypointense outer medulla on SWI showed significant differences at various time points after IRI. 12 This study further investigated the correlation between renal T A B L E 4 Receiver operating characteristic curve analysis of texture features in the differentiation of the kidney at 1 and 12 hours after reperfusion from that at 24…”
Section: Iri Time Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mie et al have investigated the feasibility of SWI on human kidneys (Mie et al, 2010). SWI signal was found to be affected by perfusion alterations and tissue fibrosis in animal models (Pan et al, 2017;J. G. Zhang et al, 2018).…”
Section: Other Mri Techniquesmentioning
confidence: 99%
“…G. Zhang et al, 2018). Pan et al have demonstrated the sensitivity of SWI after renal reperfusion where the SWI score has decreased and returned to baseline over 48h after reperfusion injury (Pan et al, 2017). Additionally, Zhang et al have shown a decrease of SWI signal ratio and a strong correlation with fibrosis staging (J. G. .…”
Section: Other Mri Techniquesmentioning
confidence: 99%